Baznas Lombok Tengah Dan Peran Pembinaan Mustahik Zakat Menjadi Muzakki - Hamdan; Agus Supriadi (TAFAQQUH, 2023)
This study aims to analyze the role of BAZNAS (National Zakat Agency) of Central Lombok Regency in implementing coaching programs to transform mustahik (zakat recipients) into muzakki (zakat payers), identify the obstacles faced, and formulate effective coaching strategies. The research employs a descriptive qualitative approach through field research with data collection techniques including in-depth interviews and observations of BAZNAS Central Lombok Regency's activities. The coaching is conducted through two approaches: physical (material) coaching, which includes ZCD programs, scholarship assistance, poor farmer empowerment, and business training; and spiritual coaching through zakat coaching classes and da'wah programs. The main obstacles include lack of honesty and transparency among mustahik, inappropriate fund utilization, limited human resources, limited fund allocation, and inadequate supervision. This research provides practical contributions for zakat managers in optimizing mustahik coaching programs and formulating transformation strategies from mustahik to muzakki through sharia-based economic empowerment.